White Matter Microstructural Damage in Small Vessel Disease Is Associated With Montreal Cognitive Assessment But Not With Mini Mental State Examination Performances: Vascular Mild Cognitive Impairment Tuscany Study. Issue 1 (January 2015) - Pasi, Marco; Salvadori, Emilia; Poggesi, Anna; Ciolli, Laura; Del Bene, Alessandra; Marini, Sandro; Nannucci, Serena; Pescini, Francesca; Valenti, Raffaella; Ginestroni, Andrea; Toschi, Nicola; Diciotti, Stefano; et al.
Abstract : Background and Purpose—: Montreal Cognitive Assessment (MoCA) has been proposed as a screening tool in vascular cognitive impairment. Diffusion tensor imaging is sensitive to white matter microstructural damage. We investigated if diffusion tensor imaging-derived indices are more strongly associated with performances on MoCA or on the widely used mini mental state examination in patients with mild cognitive impairment and small vessel disease. Methods—: Mild cognitive impairment patients with moderate/severe degrees of white matter hyperintensities on MRI were enrolled. Lacunar infarcts, cortical atrophy, medial temporal lobe atrophy and median values of mean diffusivity and fractional anisotropy of the cerebral white matter were studied and correlated with cognitive tests performances. Results—: Seventy-six patients (mean age 75.1±6.8 years, mean years of education 8.0±4.3) were assessed. In univariate analyses, a significant association of both MoCA and mini mental state examination scores with age, education, cortical atrophy, and medial temporal lobe atrophy was found, whereas mean diffusivity and fractional anisotropy were associated with MoCA. In partial correlation analyses, adjusting for all demographic and neuroimaging variables, both mean diffusivity and fractional anisotropy were associated only with MoCA (mean diffusivity: r = −0.275, P =0.023; fractional anisotropy: r =0.246, P =0.043). Conclusions—: In patients with mild cognitive impairment and small vessel disease, diffusion tensor imaging-measured white matter microstructural damage is more related to MoCA than mini mental state examination performances. MoCA is suited for the cognitive screening of patients with small vessel disease. Abstract : Supplemental Digital Content is available in the text.